ATIVIDADE ANTIOXIDANTE DE BAUHINIA BLAKEANNA DUNN (LEGUMINOSAE): caracterização, isolamento e identificação dos compostos bioativos. - SANTOS, Eyshila Evangelista do Espírito (2024)
The plant Bauhinia blakeanna dunn is known worldwide for being used as a hypoglycemic agent, that is, it is used to reduce blood glucose, acting against the disease diabetes. The aim of the work in question was to study the phytochemistry and antioxidant action of the plant's leaves. During the work, different experiments were carried out to understand its phytochemical properties, following pre-established methodologies. Among these experiments, as a basis, firstly, the processing and characterization of the powder of plant material was carried out, with the Granulometric determination of the powder being carried out, where it was possible to see that the Bauhonia blakeanna dunn powder is a coarse powder. Other important experiments were carried out on the plant powder, such as determining the swelling index, moisture content and foreign material in the powder, with results of 1.9Ml/g, 7.9% and 0.9%, respectively. Next, the standardization and characterization of the hydroethanolic extracts from the pulverized plant material was carried out and the chromatographic analyzes carried out using High Efficiency Liquid Chromatography (HPLC) were carried out. At the end of the research, the analyzes carried out helped to understand the phytochemical characteristics of the plant and its possible uses.